2015
DOI: 10.1002/2015ja020997
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐tail expansion of dipolarizing flux bundles

Abstract: Dipolarizing flux bundles (DFBs), magnetotail flux tubes with stronger, more dipolar magnetic field than the background magnetotail plasma, which are led by dipolarization fronts, typically propagate earthward within bursty bulk flows. Although DFBs are localized (typically 1–3 RE) in the cross‐tail direction, many of them may combine to cause global effects, such as the substorm current wedge. Knowledge of how this local‐to‐global coupling happens is crucial for understanding magnetotail dynamics. We investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 60 publications
5
35
0
Order By: Relevance
“…Maximum V x is achieved d t ≈40 s at R > 15 R E (green curve) and at d t ∼ 0 at R < 15 R E . The y component of the velocity does not depend on R , however, which is consistent with cross‐tail expansion of DFBs [ Liu et al , ]. An increase in [ V × B ] y is similar at all distances and lasts ≈40 to 50 s, regardless of distance.…”
Section: Discussionsupporting
confidence: 82%
“…Maximum V x is achieved d t ≈40 s at R > 15 R E (green curve) and at d t ∼ 0 at R < 15 R E . The y component of the velocity does not depend on R , however, which is consistent with cross‐tail expansion of DFBs [ Liu et al , ]. An increase in [ V × B ] y is similar at all distances and lasts ≈40 to 50 s, regardless of distance.…”
Section: Discussionsupporting
confidence: 82%
“…Assuming that P3 and P4 encountered the same DFB, we can estimate the size of the DFB's XY cross section using equation (3) of Liu, Angelopoulos, Zhou, et al (), which gives a DFB width of ~3 R E (dotted semicircles in Figure ). This width is typical for a DFB in the 6–10 R E downtail region, where it has significantly expanded in Y compared to its earlier stages (Liu et al, ). Such a typical DFB, along with its trailing DFBs (probably also with other DFBs in other local times), can excite Pi2 waves that occupy a large volume of space extending from the plasma sheet to the plasmasphere, transporting energy to both lower (Figures d and k) and higher (Figure d) L shells.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, Zhou M et al () found that some DFs originating from reconnection were quite narrow in the out‐of‐plane direction (in the tail, the out‐of‐plane direction is close to the dawn‐dusk direction). These small‐scale DFs may either expand or merge to form larger DFs during their propagation towards Earth (Liu J et al, ). We should note that these small‐scale structures may be the ripples on DFs, as reported recently in 3‐D PIC simulation and magnetospheric multiscale (MMS) observations (Vapirev et al, ; Pan DX et al, ).…”
Section: Discussion and Summarymentioning
confidence: 99%